Analysis of Ovality Deviation of Bending Superheater Tube Boiler Fabrication Process with Six Sigma Method in Manufacturing Company - Sandora, Rina; Maulidya, Syirva (UNIPA PRESS, 2024)
Quality control in fabrication is critical to the success of the production process. In this study, key factors in production quality control were identified by analyzing the influence on the tube bending process in fabrication work. Ovality deviations occur during the tube bending process that exceeds 9 percent. 30 boiler superheater tube elements had to go through the repair process. The causes of tube bending deviations were analyzed using the Six Sigma approach with the DMAIC (Define, Measure, Analyze, Improve, and Control) methodology. The causes of failure were analyzed using FMEA, and the highest RPN of 320 was obtained due to design planning and manufacturing of bending dies that are in accordance with the OD tube and the placement of clamp die and pressure die distances that are not too far apart. In addition, an RPN value of 294 was obtained due to the bending speed being too high. The recommendation for the next project is to consider using a C-Frame machine with better control to make it easier for operators to adjust the pressure, temperature, and speed of a good machine to better maintain ovality.